Why are Eastern Europe's banks not failing when everbody else's are? - Christian E. Weller; Bernard Morzuch (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
While the South East Asian financial crisis spread to Russia and Brazil, the transition economies in Central and Eastern Europe seem to be largely unaffected by international financial contagion. The lack of recent banking crises in Central and Eastern Europe is the more surprising considering that most economies have experienced severe banking sector problems in the recent past, that large bad loan ratios are still prevalent, that banking regulation and supervision are only slowly improving, and that stabilizing policies, such as capital and exchange rate controls, have slowly been eliminated. We focus on real, financial and external fundamentals compiled from the IMF's International Financial Statistics, from the World Bank's World Debt Tables, and from the BIS' Consolidated International Banking Statistics. We use univariate tests to see whether there are systematic differences between transition economies and other economies during the months leading up to a crisis, and in the months right after a banking crisis. Our results indicate that economic fundamentals during periods before and after a crisis month are generally different than non-crisis months. Also, changes in economic fundamentals are significantly different in transition economies than in other emerging economies. In particular, our results indicate that the transition economies' recent insulation from international contagion may result from a general lack of overly optimistic credit expansions. Similarly, speculative asset bubbles do not appear to have real repercussions, mainly because asset markets are underdeveloped. Because of a lack of speculative financing in transition economies, the real repercussions seem to be significantly smaller in CEECs than in other emerging economies. Thus, other risks, particularly the larger interest rate and maturity risks are less likely to materialize. As real credit is expanding more rapidly, and as asset markets become more developed, transition economies may become more similar to other emerging economies, which could lead to less insulation from international contagion in the future if adequate regulation and supervision are not implemented.
Keywords: 330; Transition economies; Central and Eastern Europe; emerging economies; banking crisis; univariate tests